2020
DOI: 10.1111/iwj.13420
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of circRNA and mRNA profiles and interactions in patients with Diabetic Foot and Diabetes Mellitus

Abstract: In order to elucidate the pathogenesis and explore new biomarkers for diabetes and diabetic foot (DF), an analysis using RNA sequencing affords broader insights into gene expression regulatory networks in DF. To better explore the molecular basis of DF, we carried out an analysis of circular RNA (circRNA) and messenger RNA (mRNA) expression profiles of serum samples from DF patients and diabetes mellitus (DM) patients. The potential roles and interactions of differentially expressed circRNAs and mRNAs were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…A number of serum biomarkers have been identified, including albumin [ 257 ], PLR and NLR [ 122 , 258 ], angiopoietin-like 2 (ANGPTL2) [ 259 ], lipoprotein-associated phospholipase A2 and interleukin-18 (IL-18) [ 260 ], pentraxin 3 [ 261 ], T-cell differentiation markers [ 262 ], stem/progenitor cells [ 263 ], as well as neutrophil extracellular traps (NETs)-specific markers [ 264 ]. Recent genomic analyses of DFU have utilized circRNAs [ 265 , 266 , 267 ], lncRNAs [ 268 ], miRNAs [ 99 , 100 , 269 ], genetic polymorphisms [ 270 , 271 , 272 ], cytokine arrays [ 273 ], and network maps [ 274 ] for the identification of other potential biomarkers for DFU diagnosis and prognosis. With the advent of bioinformatic analyses predicting factors for diabetic complications [ 275 ], the integration of computational algorithms with clinical observations and biomarker results will likely become the new standard for DFU care.…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…A number of serum biomarkers have been identified, including albumin [ 257 ], PLR and NLR [ 122 , 258 ], angiopoietin-like 2 (ANGPTL2) [ 259 ], lipoprotein-associated phospholipase A2 and interleukin-18 (IL-18) [ 260 ], pentraxin 3 [ 261 ], T-cell differentiation markers [ 262 ], stem/progenitor cells [ 263 ], as well as neutrophil extracellular traps (NETs)-specific markers [ 264 ]. Recent genomic analyses of DFU have utilized circRNAs [ 265 , 266 , 267 ], lncRNAs [ 268 ], miRNAs [ 99 , 100 , 269 ], genetic polymorphisms [ 270 , 271 , 272 ], cytokine arrays [ 273 ], and network maps [ 274 ] for the identification of other potential biomarkers for DFU diagnosis and prognosis. With the advent of bioinformatic analyses predicting factors for diabetic complications [ 275 ], the integration of computational algorithms with clinical observations and biomarker results will likely become the new standard for DFU care.…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…CircRNAs are stable and abundant and function as effective diagnostic biomarkers of stroke, like hsa_circ_0001599 (Li et al, 2021) and hsa_circ_0141720 (Chen Y. et al, 2020). In order to explore new circRNAs as potential biomarkers of AIS, ROC curves of four circRNAs (hsa_circ_0112036, hsa_circ_0066867, hsa_circ_0093708, and hsa_circ_0041685) predicted to play a role in the pathogenesis of AIS were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue-specific circRNA database showed that the major origins of differentially quantified circRNAs with tissue specificity included the digestive system, the cardiovascular system, and lungs. The diseases contributing to AIS, like hypertension, atherosclerosis, and diabetes mellitus, cause marked impairment of the cardiovascular system, disrupting the expression of circRNAs ( Wu et al, 2017 ; Zhao et al, 2020 ; Fu and Sun, 2021 ). The aberrant profile of circRNAs specific to the digestive system could be in part the result of the eating habits of patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a high throughput RNA-sequencing study, the comparison between blood samples from three just-diagnosed patients with T2D and three healthy patients unravelled a multitude of differentially expressed miRNAs, lncRNAs, circRNAs as well as mRNAs [144]. Furthermore, another RNA-sequencing study comparing patients with diabetes with and without diabetic foot complications showed that 632 mRNAs and 33 circRNAs were differently expressed in the sera of the two groups [145].…”
Section: Long Noncoding Rnas In Diabetes-related Vascular Disease: Immentioning
confidence: 99%